Komunikasi Dakwah dalam Novel Rembulan Tenggelam diwajahmu Karya Tere Liye - Siti Rohmah; Arief Ajie Pamungkas Emnoor (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to analyze the form of da'wah communication contained in the novel Rembulan Tenggelam di Wajahmu by Tere Liye. As a popular literary work, this novel not only presents an interesting storyline, but is also full of moral and religious values and da'wah messages. The research method used is a qualitative content analysis approach. Research data was obtained by identifying, classifying, and interpreting da'wah messages contained in dialogue, narrative, and character. The results show that da'wah communication in this novel is conveyed through messages of faith, sharia, and morals, which are depicted through the life journey of the main character in facing trials, regrets, and the search for the meaning of life. In addition, the author successfully presents da'wah messages that are relevant to the readers' daily lives, so that they can inspire and motivate them to strengthen the values of faith and piety. This research is expected to contribute to the study of literature-based da'wah, as well as add references regarding non-conventional da'wah media through works of fiction.